Examining career orientations at the University of Debrecen - Gergely , Éva (Applied Studies in Agribusiness and Commerce, 2016)
The paper endeavours to give a narrower definition of the orientation of ‘career’. The survey to be discussed examines a sample of 116 full time students of economics and has career anchor analysis as its focus. The study details the result of a questionnaire-based survey, which was carried out with respect to the carrier of university students and was supplemented by surveying motivation, value and work value as well. The analysis finds that “security, stability and organisational identification” are judged to be the primary career anchors among the members of the majority sample. This means that the respondents feel ready to identify themselves with the company and are looking for security to be provided by long term employment, regular earnings and by steady career advancement. The cluster analysis of the questionnaire differentiates four groups: Leaders, Specialists, Entrepreneurs and Employees. The results showed that the Leaders have high capacities of leadership, creativity and autonomy. The Specialists show highly developed functional capabilities in general and they seem to like challenges. The Entrepreneurs have outstandingly high scores concerning autonomy and entrepreneurial creativity. The members of the cluster of the Employees are characterised by a high expectation of security and stability and by low levels of managerial capability and entrepreneurial creativity. Discriminant analysis was applied to select the distinguishing features that can set the clusters apart from each other. The motivations, values preferences and work values inventory will consolidate the differences between the clusters of the career anchors. Using the method in high education within special trainings could be the practical utilization of the study. On the basis of the results a questionnaire can be compiled, which could help uncertain students relating to their carriers and future orientation containing information in connection with their carrier orientation, motivation, value preferences and work value. JEL code: I21